2017
DOI: 10.1021/acs.biochem.7b00869
|View full text |Cite
|
Sign up to set email alerts
|

Defective Nucleotide Release by DNA Polymerase β Mutator Variant E288K Is the Basis of Its Low Fidelity

Abstract: DNA polymerases synthesize new DNA during DNA replication and repair, and their ability to do so faithfully is essential to maintaining genomic integrity. DNA polymerase beta (Pol β) functions in Base Excision Repair (BER) to fill in single-nucleotide gaps, and variants of Pol β have been associated with cancer. Specifically, the E288K Pol β variant has been found in colon tumors and has been shown to display sequence-specific mutator activity. In order to probe the mechanism that may underlie E288K’s loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 34 publications
6
18
0
Order By: Relevance
“…We observed an increase in the rate of fingers closing with increasing concentrations of the complementary dNTP, as expected for an induced fit mechanism. Previous studies (18,19) found a rapid fingers closing rate of 98 s -1 , close to the maximum rate of 85 s -1 that we determined from our fit. The opening rate is concentration-dependent as well, and decreases with increasing concentrations of dTTPs.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…We observed an increase in the rate of fingers closing with increasing concentrations of the complementary dNTP, as expected for an induced fit mechanism. Previous studies (18,19) found a rapid fingers closing rate of 98 s -1 , close to the maximum rate of 85 s -1 that we determined from our fit. The opening rate is concentration-dependent as well, and decreases with increasing concentrations of dTTPs.…”
Section: Discussionsupporting
confidence: 89%
“…The distance calculated from structures 1BPX and 1BPY is significantly shorter (6.0 nm). We used the peak shift to determine the dissociation constant Kd, describing the binding affinity of DNA and Pol β, and obtained Kd = 19 ± 2 nM, in good agreement with previously published values (19,29). A trace of a single DNA molecule at [wt Pol β] = 10 nM shows excursions between the low and high FRET states (Fig.…”
Section: Pol β Bends Its Substrate But In a Different Fashion Than Csupporting
confidence: 85%
See 3 more Smart Citations